Polarisation profiles of southern pulsars at 3.1 GHz - Karastergiou, A; Johnston, S; Manchester, R (2005)
We present polarisation profiles for 48 southern pulsars observed with the new 10-cm receiver at the Parkes telescope. We have exploited the low system temperature and high bandwidth of the receiver to obtain profiles which have good signal to noise for most of our sample at this relatively high frequency. Although, as expected, a number of profiles are less linearly polarised at 3.1 GHz than at lower frequencies, we identify some pulsars and particular components of profiles in other pulsars which have increased linear polarisation at this frequency. We discuss the dependence of linear polarisation with frequency in the context of a model in which emission consists of the superposition of two, orthogonally polarised modes. We show that a simple model, in which the orthogonal modes have different spectral indices, can explain many of the observed properties of the frequency evolution of both the linear polarisation and the total power, such as the high degree of linear polarisation seen at all frequencies in some high spin-down, young pulsars. Nearly all the position angle profiles show deviations from the rotating vector model; this appears to be a general feature of high-frequency polarisation observations.